Dinamika Etika dan Kompetensi Konselor Dalam Layanan Bimbingan dan Konseling : Tinjauan Studi Literatur - Adela, Nurul; N, Nurfarhanah; Ardi, Zadrin (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Guidance and Counseling (BK) plays a crucial role in supporting individuals’ optimal development across academic, social, personal, and career aspects. The effectiveness of counseling services relies heavily on two key elements: ethics and counselor competence. Ethics serve as a moral framework that ensures integrity, confidentiality, and professionalism in the counseling relationship, while competence reflects the counselor’s knowledge, skills, and professional attitude in managing various client issues. This study uses a descriptive qualitative method with a literature review approach, aiming to examine the interrelation between ethics and competence in counseling practice. The findings highlight that integrating ethical principles with professional competence is essential in establishing effective, safe, and client-centered counseling services. Counselors are expected to continuously enhance their capabilities through ongoing education, training, and updated ethical understanding aligned with technological and societal developments.